Europeanization and the varying responses in collective skill systems - Powell, Justin J. W. [Verfasser]; Trampusch, Christine [Verfasser] (My University, 2012)
"Europeanization elicits varying responses in collective skill systems, which are still mainly governed in national contexts and determined primarily by domestic politics. This chapter explores the impact of Europe, and the European Union in particular, on contemporary conflicts and consensus and on institutional change in vocational training regimes. We analyze the impact of the European level on national institutions responsible for skill formation and explore similar challenges posed by European initiatives and the different responses of the collective skill systems. Investigating the two levels and their interaction, we contrast countries in which conflicts over such forms of Europeanization have ensued - Germany and Switzerland - with those in which consensus has facilitated Europeanization - Austria, Denmark, and the Netherlands." (Autorenreferat, BIBB-Doku)
Keywords: S 2.3 Berufsbildungspolitik; I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; I 2.2 Europa; EU-Bildungspolitik; Europäische Integration; Europäischer Qualifikationsrahmen; Nationaler Qualifikationsrahmen; Europäisches Leistungspunktesystem; Internationaler Vergleich; Bundesrepublik Deutschland; Dänemark; Niederlande; Österreich; Schweiz